Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jfpe.12308
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Infrared Heating and Its Application in Drying of Food Materials: A Review

Abstract: Drying is an energy-intensive unit operation in chemical, food and allied industries. It is always desired to have low energy consumption for drying operation without compromising the quality of products. In this review, fundamental aspects of infrared heating are described in detail with the focus on its application to the drying of food materials. The modeling techniques are explained in detail to get emphasis on the design of large-scale infrared dryers. This review also contains the investigations carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 80 publications
0
42
0
Order By: Relevance
“…Infrared (IR) radiation belongs to electromagnetic radiations with the wavelength range of 0.78-1,000 μm (Pawar and Pratape 2017). Water and organic materials such as carbohydrates, fats and proteins are the main ingredients of foodstuffs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared (IR) radiation belongs to electromagnetic radiations with the wavelength range of 0.78-1,000 μm (Pawar and Pratape 2017). Water and organic materials such as carbohydrates, fats and proteins are the main ingredients of foodstuffs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Like other electromagnetic waves, the transmission of IR energy does not require media. The energy emitted from the IR lamp directly reaches the materials and does not heat the surrounding air (Pawar and Pratape 2017). When the wavelength of the radiation source coincides with the absorption wavelength of the irradiated object, the substance absorbs a large amount of infrared energy, thereby altering and aggravating the movement of its molecules and achieving the effect of…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Comparing with traditional drying methods, FIR drying could achieve higher rate of heat and mass transfer. There are several significant advantages of FIR drying including short drying time, high energy efficiency, uniform heating, and high quality of dried products (Pawar & Pratape, 2017). Several studies have reported about FIR drying of agricultural products including strawberry (Adak, Heybeli, & Ertekin, 2017), rice (Khir, Pan, Salim, Hartsough, & Mohamed, 2011), longan (Nathakaranakule, Jaiboon, & Soponronnarit, 2010), red ginseng (Ning & Han, 2013), and jujube (Doymaz, Karasu, & Baslar, 2016), and the results showed that FIR heating could promote dehydration rate and improve product quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, drying process can decrease the product quality especially nutritional value and therefore the drying method to be used has to be selected correctly and the operating conditions should be adjusted. It is thought that infrared radiation can be used as an alternative to the production of healthy snack products, such as fruit bars due to its ability to penetrate the product quickly, to save energy considerably, and to have lower nutritional loss than conventional methods (Nowak & Lewicki, ; Pawar & Pratape, ; Riadh, Ahmad, Marhaban, & Soh, ). Besides the choice of suitable drying method, the modeling of the drying process is very important in terms of optimizing the product quality and reducing operational costs.…”
Section: Introductionmentioning
confidence: 99%